2010
DOI: 10.1111/j.1744-7410.2010.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a fluctuating thermal regime on adult and larval reef corals

Abstract: We compared responses of adults and larvae of the brooding corals Pocillopora damicornis and Seriatopora hystrix to 12-h exposures to constant temperature treatments (211C, 281C, or 301C) and a treatment in which temperature fluctuated from 281 to 211C, simulating daily temperature variation generated by tidally driven upwelling in their natural habitat (Nanwan Bay, southern Taiwan). In all treatments, the maximum dark-adapted quantum yield of photosystem II (F V /F M ) of the larvae was B49% lower than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
51
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 61 publications
10
51
0
Order By: Relevance
“…Most studies, however, concentrate on the influence of increased temperatures (e.g., Brown et al 2000;Oliver and Palumbi 2011;Barshis et al 2013). Yet studies on corals influenced by cold water fluctuations have indicated that these corals exhibit enhanced heat resistance due to supposed acclimations to recurring stress (Putnam et al 2010;Mayfield et al 2013). This study concords with this hypothesis, since LAIW-exposed corals used to large short-term variations in temperature were less affected by variations from longterm average temperatures than sheltered corals (see also McClanahan et al 2007a;Oliver and Palumbi 2011).…”
Section: Discussionsupporting
confidence: 73%
“…Most studies, however, concentrate on the influence of increased temperatures (e.g., Brown et al 2000;Oliver and Palumbi 2011;Barshis et al 2013). Yet studies on corals influenced by cold water fluctuations have indicated that these corals exhibit enhanced heat resistance due to supposed acclimations to recurring stress (Putnam et al 2010;Mayfield et al 2013). This study concords with this hypothesis, since LAIW-exposed corals used to large short-term variations in temperature were less affected by variations from longterm average temperatures than sheltered corals (see also McClanahan et al 2007a;Oliver and Palumbi 2011).…”
Section: Discussionsupporting
confidence: 73%
“…Q m , an indicator of the excitation pressure over PSII, was reduced in fluctuating treatments, reflecting a stronger competitiveness of photochemical process for reaction centers over non-photochemical quenching (Iglesias-Prieto et al, 2004). The higher F /F m and lowered Q m under fluctuating conditions suggest that the diel temperature oscillations could relieve heat stress on corals and corroborate previous findings that temperature fluctuations are favorable to the photo-physiology of corals (Mayfield et al, 2012;Putnam et al, 2010). The positive effect of exposure to fluctuating temperatures on these photophysiological metrics may be associated with the cooling overnight and upregulation of the genes related to photosynthesis (Mayfield et al, 2012).…”
Section: Symbiont Responses To Elevated and Fluctuating Temperaturessupporting
confidence: 77%
“…For instance, the photo-physiology in larval and adult pocilloporid corals is more adapted to fluctuating temperatures (Putnam et al, 2010;Mayfield et al, 2012). Conversely, significant reductions in photochemical efficiency, symbiont density and aerobic respiration were found in corals exposed to fluctuating temperatures compared to those in constant temperatures Edmunds, 2008, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations